2018
DOI: 10.1128/jvi.00105-18
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Primary Human Choroid Plexus Epithelial Cells and Meningeal Cells to Infection by JC Virus

Abstract: JC polyomavirus (JCPyV) establishes a lifelong persistence in roughly half the human population worldwide. The cells and tissues that harbor persistent virus are not known, but renal tubules and other urogenital epithelial cells are likely candidates as virus is shed in the urine of healthy individuals. In an immunosuppressed host, JCPyV can become reactivated and cause progressive multifocal leukoencephalopathy (PML), a fatal demyelinating disease of the central nervous system. Recent observations indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 70 publications
(81 reference statements)
1
41
0
Order By: Relevance
“…Our hypothesis is supported by the in vivo demonstration of JCPyV infected choroid plexus epithelial cells and meningeal cells from a patient with meningitis and from several patients with PML [28,29]. We also previously reported that the choroid plexus, like cells in the kidney, express the JCPyV attachment and entry receptors, bind virus in human tissue sections, and are completely susceptible to virus infection in vitro [17,27]. This is in contrast to human macroglial cells that do not express the critical attachment receptor for the virus and do not bind virus in human tissue sections [17].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our hypothesis is supported by the in vivo demonstration of JCPyV infected choroid plexus epithelial cells and meningeal cells from a patient with meningitis and from several patients with PML [28,29]. We also previously reported that the choroid plexus, like cells in the kidney, express the JCPyV attachment and entry receptors, bind virus in human tissue sections, and are completely susceptible to virus infection in vitro [17,27]. This is in contrast to human macroglial cells that do not express the critical attachment receptor for the virus and do not bind virus in human tissue sections [17].…”
Section: Discussionsupporting
confidence: 77%
“…JCPyV to human glia in EV independently of the known sialic acid attachment receptor LSTc [22,[26][27][28][29][30]. To study the role of choroid plexus derived extracellular vesicles in dissemination of JCPyV to the CNS in depth we immortalized primary human choroid plexus epithelial cells with human telomerase (hTert) and showed that they maintain the properties of the primary cells.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…During states of immunosuppression, it is possible for the latent CNS BK virus to reactivate and cause meningoencephalitis 10 . In fact, JC virus has been shown to infect the primary choroid plexus epithelial cells and meningeal cells, using these cells as reservoirs for the subsequent invasion of brain parenchyma 12 . However, since BK virus DNA has been detected in the brain tissue and CSF of immunocompetent individuals as well, a mere presence of virus is not a proof of a causal relationship between neurological symptoms and the virus 13‐15 .…”
Section: Discussionmentioning
confidence: 99%
“…A very limited number of studies have been conducted with CP epithelial cells with respect to neuroinvasion. John Cunningham virus and Chikungunya virus are known to infect CP epithelial cells in vitro (37,68); however, to our knowledge, our study shows for the first time neurotropic viruses traversing the CP epithelial cell layers without active replication. Importantly, interferon gamma (IFN-γ), the Th2-type cytokine interleukin-4 (IL-4), and MPC-1 are known to enhance transcytosis of IgA and HIV (69,70).…”
Section: Discussionmentioning
confidence: 58%